Entrepreneurship within the young migrant’s Cabo Verde population - Gomes, Melanie (2018)
Entrepreneurship is vital for the growth and development of a country. This is particularly true for African countries in developing stages where entrepreneurship is fundamental to boost job creation, alleviate poverty and promote the return of the young migrant population. Through qualitative (exploratory interviews) and quantitative methodological approaches (surveys and their statistical analysis) the present research work intends to understand the importance of the entrepreneurship intentions among a sample of Cabo Verde young migrants and Cabo Verde young entrepreneurs. It also intends to understand if the political, economic and social environment is the one that is the most suitable and likely to encourage the creation of new firms among the young population in Cabo Verde.